Óbitos intra e extra-hospitalares por infarto agudo do miocárdio nas capitais brasileiras - ABREU, Sterffeson Lamare Lucena de (2018)
INTRODUCTION: Acute myocardial infarction (AMI) is the leading cause of death in Brazil and worldwide. Approximately 42% of deaths occur outside the hospital. OBJECTIVE: To analyze the distribution and sociodemographic characteristics of inand out-of-hospital deaths by AMI in Brazilian capitals cities and their relationship with municipal development indicators. METHODS: An ecological study was conducted with the annual count of AMI deaths in the 27 Brazilian capitals cities from 2007 to 2016. The deaths were divided into two groups: in-hospital and out-of-hospital. Annual mortality rates were calculated by capital city and for all the capitals cities. The sociodemographic differences gender, age, schooling, marital status and skin color were compared between the groups by chi-square. Negative binomial regression models were adjusted for each of the groups with the death count and the independent variables: residing in the South and Southeast regions, municipal human development index (IDHM), Gini index and expected years of study. Statistical analysis was performed using Stata® v.14 software. RESULTS: In all the capitals, there was a rise in extrahospital mortality over time. All the sociodemographic characteristics surveyed were statistically different between the groups (p <0.001). Comparatively in the out-ofhospital group there was more deaths in men, octagenarians, as well as reduction of deaths in married patients. Residency in the South and Southeast regions increased the indication of extra-hospital deaths (IRR=2.84, 95%CI=1.67-4.85), while higher expectation of years of study decreased it (IRR=0.86, 95%CI = 0.77-0.97). For the intrahospital group, higher HDI was related to a decrease in the incidence of in-hospital deaths (RR = 0.44, 95% CI = 0.33-0.58), while higher expectation of years of study increased incidence (IRR = 1.09, 95%CI =1.03-1.15). CONCLUSION: The rates of out-of-hospital mortality due to AMI are increasing over time in Brazilian capitals cities. Compared to in-hospital deaths, out-of-hospital deaths were more prevalent in men, octagenarians, non-elderly and unmarried. There was a higher incidence of out-ofhospital deaths in the residents of the South and Southeast regions, while in the cities with the highest HDI, there was a reduction in in-hospital deaths. Capitals with the highest expectation of years of study moved the deaths from the out-of- to the inhospital.